An Argumentative Approach to “Framing”. Framing, Deliberation and Action in an Environmental Conflict (2020)
This paper proposes a new theorization of the concept of “framing”, in which argumentation has a central role. When decision-making is involved, to frame an issue is to offer the audience a salient and thus potentially overriding premise in a deliberative process that can ground decision and action. The analysis focuses on the Roşia Montană case, a conflict over policy that developed over the years into an environmental social movement and, in September 2013, culminated in the most significant public protests in Romania since the 1989 Revolution. Starting from Entman’s understanding of framing as “selection and salience”, several framing strategies are identified and discussed, illustrating three main mechanisms. The way in which “selection and salience” operates via a range of argument schemes in a deliberative, decision-making process, in order to produce framing effects (including, possibly, collective mobilization) is illustrated with examples from the 2013 campaign and protests (slogans, websites, blogs and newspaper articles).